A present without future? Youth, education and family in Tunisia - Garcia, Jose Sánchez; Najar, Sihem (Rizoma freireano, 2019)
Keywords: Vie sociale – Djerba

جوانب من التاريخ الاجتماعي والثقافي الإباضي من خلال كتاب" المعلقات في أخبار وروايات أهل الدعوة" لمؤلف مجهول (ق6هـ/12م) - حمامد, محمد (الساورة للدراسات الانسانية والاجتماعية, 2024)
تعالج هذه الورقة البحثية الأوضاع الاجتماعية و الثقافية الإباضية من خلال كتاب" المعلقات في أخبار وروايات أهل الدعوة" لمؤلف مجهول (القرن السادس الهجري /الثاني عشر الميلادي)، بالوقوف على العادات والتقاليد والمنجزات العلمية الإباضية. عبر إشكالية تبحث في مظاهر الحياة الاجتماعية والثقافية ومميزاتها العامة. Abstract: This research paper addresses the Ibadi social and cultural conditions through the book “Al-Mu’allaqat fi Akhbar and Narrations of the People of the Call” by an unknown author (6 AH/12 AD) by identifying customs, traditions, and scientific achievements through a problem that examines the aspects of social and cultural life and its general characteristics
Keywords: Prosopographie – Djerba; Vie sociale – Djerba